O niektórych aspektach antagonizowania się kultur w społeczności turystów i mieszkańców. Rozważania na kanwie teorii dezorganizacji i organizacji społecznej Thomasa i Znanieckiego - Tomaszewska, Monika (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
The aim of the article is to indicate the possibility of using the theory of social organization and disorganization of Thomas and Znaniecki to analyze the conflictual behavior and attitudes occurring in social relations between tourists and residents.
Keywords: tourists; residents; tourists relations – residents; disorganization theory and social organization